Utility of Chest Computed Tomography after a "Normal" Chest Radiograph in Patients with Thoracic Stab Wounds. Issue 10 (October 2015) - Nguyen, Brian M.; Plurad, David; Abrishami, Sadaf; Neville, Angela; Putnam, Brant; Kim, Dennis Y.
Chest computed tomography (CCT) is used to screen for injuries in hemodynamically stable patients with penetrating injury. We aim to determine the incidence of missed injuries detected on CCT after a negative chest radiograph (CXR) in patients with thoracic stab wounds. A 10-year retrospective review of a Level I trauma center registry was performed on patients with thoracic stab wounds. Patients who were hemodynamically unstable or did not undergo both CXR and CCT were excluded. Patients with a negative CXR were evaluated to determine if additional findings were diagnosed on CCT. Of 386 patients with stab wounds to the chest, 154 (40%) underwent both CXR and CCT. One hundred and fifteen (75%) had a negative screening CXR. CCT identified injuries in 42 patients (37%) that were not seen on CXR. Pneumothorax and/or hemothorax occurred in 40 patients (35%), of which 14 patients underwent tube thoracostomy. Two patients had hemopericardium on CCT and both required operative intervention. Greater than one-third of patients with a normal screening CXR were found to have abnormalities on CCT. Future studies comparing repeat CXR to CCT are required to further define the optimal diagnostic strategy in patients with stab wounds to chest after normal screening CXR.